Renal Transplant Complications: Diagnostic and Therapeutic Role of Radiology. Issue 3 (August 2014) - Inci, Mehmet Fatih; Ozkan, Fuat; See, Teik Choon; Tatli, Servet
Kidney was the first and is the most frequently transplanted organ. Despite improved surgical techniques and transplantation technology, complications do occur and, if left untreated, may lead to catastrophic consequences. Renal transplantation complications may be vascular (eg, renal artery and vein stenosis and thrombosis, arteriovenous fistula, and pseudoaneurysms); urologic (eg, urinary obstruction and leak, and peritransplantation fluid collections, including hematoma, seroma, lymphocele, and abscess formation); and nephrogenic, including acute tubular necrosis, graft rejection, chronic allograft nephropathy, and neoplasm. Early diagnosis and treatment of these complications are paramount to prevent graft failure and other significant morbidities to the patients. Radiology plays a pivotal role in the diagnosis and treatment of these complications, with minimally invasive percutaneous techniques. In this article, we reviewed renal transplantation anatomy, a wide range of complications that may occur after renal transplantation surgery, typical imaging appearances of the complications on varies imaging modalities, and percutaneous interventional techniques that are used in their treatment.